2011
DOI: 10.1103/physreve.83.041907
|View full text |Cite
|
Sign up to set email alerts
|

Towards quantitative classification of folded proteins in terms of elementary functions

Abstract: A comparative classification scheme provides a good basis for several approaches to understand proteins, including prediction of relations between their structure and biological function. But it remains a challenge to combine a classification scheme that describes a protein starting from its well-organized secondary structures and often involves direct human involvement, with an atomary-level physics-based approach where a protein is fundamentally nothing more than an ensemble of mutually interacting carbon, h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(96 citation statements)
references
References 13 publications
1
90
0
5
Order By: Relevance
“…Elsewhere [11], [12] it has been shown that loops in the chicken villin headpiece with PDB code 1YRF and the myoglobin 1ABS can be described in terms of the dark soliton of the generalized discrete nonlinear Schrödinger equation that derives from the energy function…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Elsewhere [11], [12] it has been shown that loops in the chicken villin headpiece with PDB code 1YRF and the myoglobin 1ABS can be described in terms of the dark soliton of the generalized discrete nonlinear Schrödinger equation that derives from the energy function…”
Section: Modelmentioning
confidence: 99%
“…The soliton evokes a deformation of the protein shape, and as a consequence a trapped soliton is a natural cause for protein folding. The present generalization of the original DNLS equation is motivated by recent observations that protein loops in the HP35 villin headpiece with Protein Data Bank (PDB) [10] code 1YRF [11], and in the myoglobin with PDB code 1ABS [12] are accurately described in terms of its dark soliton. In this article we extend this observation to essentially all proteins in PDB.…”
Section: Introductionmentioning
confidence: 99%
“…But we have found [32][33][34] that an excellent approximative solution can be obtained by discretizing the topological soliton (43).…”
Section: Discretized Solitonsmentioning
confidence: 99%
“…Hence we compensate for the extension of κ to negative values, by engaging a discrete Z 2 symmetry [33]. An (isolated) point where the curvature κ(s) vanishes is an inflection point.…”
Section: Frame Anomalymentioning
confidence: 99%
“…But a numerical approximation can be easily constructed using the procedure described in [11]. Furthermore, since it turns out that in the case of proteins the first term in (25) is small, an excellent approximation [12] is given by the naive discretization of the continuum dark NLSE soliton [20],…”
Section: D: Soliton Ansatzmentioning
confidence: 99%